2001
DOI: 10.1074/jbc.c100613200
|View full text |Cite
|
Sign up to set email alerts
|

Caveolae-deficient Endothelial Cells Show Defects in the Uptake and Transport of Albumin in Vivo

Abstract: The role of endothelial cell caveolae in the uptake and transport of macromolecules from the blood-space to the tissue-space remains controversial. To address this issue directly, we employed caveolin-1 gene knock-out mice that lack caveolin-1 protein expression and caveolae organelles. Here, we show that endothelial cell caveolae are required for the efficient uptake and transport of a known caveolar ligand, i.e. albumin, in vivo. Caveolin-1-null mice were perfused with 5-nm gold-conjugated albumin, and its u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
221
4
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 303 publications
(245 citation statements)
references
References 53 publications
(36 reference statements)
19
221
4
1
Order By: Relevance
“…First, we demonstrated that LacCer internalization occurred by a clathrin-independent mechanism using multiple pathway-specific inhibitors as well as a DN construct of Eps15 that blocks clathrin-dependent endocytosis (Figure 2), consistent with our previous results in HSFs (Puri et al, 2001). Second, we showed that the fluorescent LacCer analog colocalized with fluorescently labeled albumin (Figure 3), which is reported to be internalized via caveolae in other cell types (Shubert et al, 2001). Furthermore, both the LacCer analog and fluorescent albumin extensively colocalized with DsRed-cav-1 in RFs at an early stage (2 min) of internalization (Figure 4).…”
Section: Bodipy-laccer Is Internalized By Caveolaesupporting
confidence: 77%
See 3 more Smart Citations
“…First, we demonstrated that LacCer internalization occurred by a clathrin-independent mechanism using multiple pathway-specific inhibitors as well as a DN construct of Eps15 that blocks clathrin-dependent endocytosis (Figure 2), consistent with our previous results in HSFs (Puri et al, 2001). Second, we showed that the fluorescent LacCer analog colocalized with fluorescently labeled albumin (Figure 3), which is reported to be internalized via caveolae in other cell types (Shubert et al, 2001). Furthermore, both the LacCer analog and fluorescent albumin extensively colocalized with DsRed-cav-1 in RFs at an early stage (2 min) of internalization (Figure 4).…”
Section: Bodipy-laccer Is Internalized By Caveolaesupporting
confidence: 77%
“…To further characterize the endocytosis of LacCer, we carried out colocalization experiments using labeled albumin, which internalizes via caveolae in some cell types (Shubert et al, 2001). In preliminary studies, we found that internalization (5 min at 37°C) of fluorescent albumin was inhibited by 88.9 Ϯ 6.8% in cells pretreated with nystatin, similar to that seen using LacCer and CtxB (Figure 2A), but was inhibited by only 7.2 Ϯ 1.7% following pretreatment with CPZ.…”
Section: Endocytosis Of Multiple Gsl Analogs In Rat Fibroblastsmentioning
confidence: 99%
See 2 more Smart Citations
“…Caveolin-deficient mice have given novel insight into the function of caveolae. Caveolin-1 gene knockout leads to pulmonary defects, vasoconstriction, or dilatation abnormalities and resistance to diet-induced obesity (Drab et al, 2001;Razani et al, 2001;Schubert et al, 2001;Sotgia et al, 2002;Razani et al, 2002). Simian virus 40 (SV40) has been shown to be internalized through caveolae and detailed studies focused on the virus entry mechanism have produced a lot of new information about the biology of caveolae (Pelkmans et al, 2001.…”
Section: Introductionmentioning
confidence: 99%